A new species of Drupeus Lewis from eastern China (Coleoptera: Ptilodactylidae: Cladotominae) - Hájek, Jiří (Zootaxa, 2021)
Drupeus guadunensis sp. nov. is described from hygropetric habitats in Wuyishan National Nature Reserve, Fujian Province, China. The new species is similar in habitus and genitalia to its congeners; however, it can be distinguished based on the more distinctly flabellate antennae in the male, and greatly elongate antennomere III in the female; in addition the new species is characteristic with the presence of a well delimited dark spot in the anterior part of the pronotum. The diagnostic characters of the new species are illustrated, as well as habitus of both previously recorded Chinese Drupeus Lewis, 1895 species.